Socio-economic and Political Deprivation of Hill Dalits (A Study of Gaikhur and Taple Villages of Gorkha District) - Khanal, Shiva Prasad (Voice of Teacher, 2022)
This paper applies the mix-method approach (both quantitative and qualitative methods) through survey data from Gaikhur and Taple villages of Gorkha district (408 Hill Dalit households and 210 non-Dalit households).The caste hierarchy and varna system created the caste-based discrimination and untouchability practice in Nepal. This paper also explores that because of caste-based discrimination including untouchability prevailed in the villages studies non-Dalits discriminates Dalits in education and participation inreligious and cultural functions in the villages. Further, Dalits are deprivedof household income generation as compared to that of non-Dalits. Data also reveals that Dalits are deprived of political participation as compared to that of non-Dalits. Within Hill Dalits, the so-called low caste Dalits (Damai and Gaine) have also deprived in education, household income and political as well as cultural participation as compared to that of high caste Dalits (Sarki and Kami).